Islamic Religious Education Learning in Developing Students' Spiritual Quotient - Diah Ayu Sekar Kinanthi; Saepul Mukti; Abdurrahman Saleh (Global Education Journal, 2026)
This study is motivated by the importance of developing students' Spiritual Quotient (SQ) through Islamic Religious Education (PAI) learning amidst various moral and social challenges faced by adolescents. The study aims to describe the implementation of Islamic Religious Education learning, its role in developing students' Spiritual Quotient, and its implications for students at SMP Negeri 2 Purwakarta. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The study adopted Danah Zohar and Ian Marshall's Spiritual Quotient theory, which includes self-awareness, the ability to overcome difficulties, reluctance to cause harm, and spiritual and religious intelligence. The findings revealed that students' Spiritual Quotient was developed through religious habituation, teacher role modeling, moral guidance, reflection on religious values, and religious activities within the school environment. Islamic Religious Education learning had positive implications for improving self-awareness, the ability to face difficulties, social concern, and the practice of religious values in daily life. Keywords: Islamic Religious Education, Spiritual Quotient, spiritual intelligence, students.